All fours ebook A novel. - July, Miranda (2024)
A NEW YORK TIMES TOP TEN BOOK OF THE YEAR A WASHINGTON POST NOTABLE BOOK OF THE YEAR ONE OF TIME MAGAZINE’S TOP 10 FICTION BOOKS OF 2024 ONE OF NPR’S “BOOKS WE LOVE” 2024 NAMED A BEST BOOK OF THE YEAR BY: THE NEW YORKER ● VOGUE ● FINANCIAL TIMES ● OPRAH DAILY ● VULTURE ● VOX The New York Times bestselling author returns with an irreverently sexy, tender, hilarious and surprising novel about a woman upending her life “A frank novel about a midlife awakening, which is funnier and more boldly human than you ever quite expect . . . nothing short of riveting .” —Vogue “ All Fours has spurred a whisper network of women fantasizing about desire and freedom. . . . It’s the talk of every group text." —The New York Times “ All Fours possessed me. I picked it up and neglected my life until the last page, and then I started begging every woman I know to read it as soon as possible.” — The Cut A semi-famous artist announces her plan to drive cross-country, from LA to NY. Thirty minutes after leaving her husband and child at home, she spontaneously exits the freeway, checks into a nondescript motel, and immerses herself in an entirely different journey. Miranda July’s second novel confirms the brilliance of her unique approach to fiction. With July’s wry voice, perfect comic timing, unabashed curiosity about human intimacy, and palpable delight in pushing boundaries, All Fours tells the story of one woman’s quest for a new kind of freedom. Part absurd entertainment, part tender reinvention of the sexual, romantic, and domestic life of a forty-five-year-old female artist, All Fours transcends expectation while excavating our beliefs about life lived as a woman. Once again, July hijacks the familiar and turns it into something new and thrillingly, profoundly alive.